„Zrozumieć tonalność na nowo”: wokół książki Dmitriego Tymoczki A Geometry of Music. Harmony and Counterpoint in the Extended Common Practice - Iwańska, Ilona (Res Facta Nova, 2025)
The article is an extended review of the famous and important book by Dmitri Tymoczko entitled A Geometry of Music. Harmony and Counterpoint in the Extended Common Practice. It is largely a summary of the author's theory presented in the book, based on several key pillars. The first is a new concept of tonality, defining its five components, such as: conjunct melodic motion; acoustic consonance; harmonic consistency; limited macroharmony; centricity. The second pillar concerns four basic claims about the mutual constraints between the features indicated above. They shall read as follows: Harmony and counterpoint constrain one another; Scale, macroharmony, and centricity are Independent; Modulation involves voice leading; Music can be understood geometrically. The third pillar is an impressive musical- geometric model, which, according to Tymoczko's own declaration, rebuilds the „musical set theory from the ground up”. Finally, the fourth pillar is the thesis about the existence of an „extended common practice”, stretching from the eleventh century to the present day. A counterpoint to the content described above are comments on the structure of the book and the author's writing style, digressions on the relationship between his thoughts and the neo-Riemannian paradigm, and an ongoing assessment of the theoretical tools described. The summary brings the conclusion that the author's most valuable contribution to the development of the field is his universal theory of harmony. Paradoxically, musical geometry is considered to be the least useful aspect of the book, at least from the perspective of its potential reception in musical analysis.